2022
DOI: 10.1097/ta.0000000000003615
|View full text |Cite
|
Sign up to set email alerts
|

Delayed splenic pseudoaneurysm identification with surveillance imaging

Abstract: Routine follow up imaging after splenic injury identifies splenic artery pseudoaneurysm in a significant proportion of patients. Standardized surveillance imaging promotes prospective identification of pseudoaneurysms, allowing for interventions to maximize splenic salvage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…SPA formation and presence is an important risk factor for consideration of DSR, even in cases of minor splenic injuries [15] . Previous literature supports that routine CT follow-up identifies a significant proportion of patients with SPA; thus, repeated CT screening for SPAs may aid in identifying patients most at risk for DSR [23] . Furthermore, most delayed splenic vascular injuries have also been noted to be only detected on or are much more conspicuous on arterial phase CT scan imaging versus with portal-venous CT scan [17] .…”
Section: Discussionmentioning
confidence: 90%
“…SPA formation and presence is an important risk factor for consideration of DSR, even in cases of minor splenic injuries [15] . Previous literature supports that routine CT follow-up identifies a significant proportion of patients with SPA; thus, repeated CT screening for SPAs may aid in identifying patients most at risk for DSR [23] . Furthermore, most delayed splenic vascular injuries have also been noted to be only detected on or are much more conspicuous on arterial phase CT scan imaging versus with portal-venous CT scan [17] .…”
Section: Discussionmentioning
confidence: 90%
“…A recent retrospective evaluation of adult splenic injuries from a level I trauma center in the United States reported that a relatively high proportion of patients who developed PA required subsequent splenectomy. 26 Despite the fact that some patients who undergo distal embolization of the splenic artery experience minor spleen infarcts, the procedure itself rarely results in splenectomy. 24,27 Conversely, if proximal embolization is performed on admission angiography and then a PA develops in the late phase, vascular access to the splenic artery during "secondlook" angiography is limited.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of data regarding the use of IR in children, most of our knowledge on this topic is extrapolated from the adult literature. A recent retrospective evaluation of adult splenic injuries from a level I trauma center in the United States reported that a relatively high proportion of patients who developed PA required subsequent splenectomy 26 . Despite the fact that some patients who undergo distal embolization of the splenic artery experience minor spleen infarcts, the procedure itself rarely results in splenectomy 24,27 .…”
Section: Discussionmentioning
confidence: 99%
“…We agree that, despite multiple previous studies on this topic, it is still controversial whether follow-up imaging would be beneficial to prevent the feared complications of delayed splenic PSA (i.e., rupture) following successful nonoperative management (NOM). However, we believe that the results of Wallen et al 1 should be interpreted carefully for several reasons.…”
mentioning
confidence: 91%
“…We read with interest the article by Wallen et al, 1 who reported that delayed formation of splenic pseudoaneurysm (PSA) was identified on follow-up computed tomography (CT) scan in 20% of patients with high-grade blunt splenic injury (BSI) managed nonoperatively (11%, 29%, and 40% in Grades III, IV, and V, respectively). We agree that, despite multiple previous studies on this topic, it is still controversial whether follow-up imaging would be beneficial to prevent the feared complications of delayed splenic PSA (i.e., rupture) following successful nonoperative management (NOM).…”
mentioning
confidence: 99%